Using Artificial Intelligence (AI) to improve accounting productivity and performance in business - Abdul Rahman, Samsuria; Wan Mustafa, Wan Muzlaina; Mat Jusoh, Yusri Huzaimi (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Accounting is one of the critical aspects of managing a business. Accuracy in managing finances, reporting transactions, and making good financial planning can affect the success or failure of a business. With the latest technological advancements, artificial intelligence (AI) is now playing an increasingly important role in improving accounting productivity and performance. This article explores how AI can improve performance and efficiency in the accounting field and provide advantages to business. 1. Automate Routine Accounting Tasks One of the main ways AI is improving productivity in accounting is through the automation of routine tasks. Tasks such as bookkeeping, invoice generation, account reconciliation, and receipt management can now be handled by AI software. AI-based accounting systems can automatically process transactions, classify those transactions by category, and generate financial reports without the need for extensive manual input. Examples: Invoice Generation - AI can detect and create invoices based on transaction data available in the system; reducing human error and increasing efficiency. Bank Reconciliation - AI can automatically review bank transactions and ensure that financial records match bank records; saving time and effort in the reconciliation process.